Une réalité : Un groupe de recherche bilingue - Allard, Michel (Canadian Journal of Education/Revue canadienne de l'éducation, 1977)
Established in 1969, the Montreal-Toronto Research Group, funded by the Canada Studies Foundation, engaged until 1975 in action research in the teaching of history. Made up of teachers at the secondary, college (CEGEP) and university levels from the Montreal and Toronto regions, this group faced the problems inherent in the fact that its members came from two different cultural milieux with differing interpretations of Canadian history, divergent teaching methods, and different languages. The group sought to develop source teaching materials meeting the following criteria: they should serve as media integrated with history textbooks, other teaching tools, and historical sources (and thus should be selective rather than exhaustive in their coverage); be historically valid; be comprehensible and interesting to secondary school pupils; present diverse, even contradictory, historical interpretations; include primary source materials, again often contradictory; be focussed on historical periods rather than on specific events (1713–1760, 1830–1840, 1868–1891); be accompanied by a teachers' guide. The materials were assembled, tried out in classrooms in both cities, and evaluated by members of the group. The result was a series of teaching units which are now in the process of publication in both languages. A detailed report of the experience of the group is available from the Canada Studies Foundation.